Falsafah Sipakatau, Sipakalebbi, Sipakainge' dalam Perspektif Moderasi Beragama dan Hukum Islam: Kajian Etnografi pada Masyarakat Bugis Sorong Papua - Sudirman, Sudirman; Ramli, Muhammad; Iskandar, Iskandar; Huzain, Muh. (Institut Agama Islam Negeri Kendari, 2023)
Although research on the Sipakatau, Sipakalebbi, Sipakainge’ philosophy has been widely discussed by scholars, few have analyzed them from the perspective of religious moderation and Islamic law. This article aims to discuss the Sipakatau, Sipakalebbi, Sipakainge' traditions from the perspective of religious moderation and Islamic Law among the Bugis community in Sorong, Papua. This study uses an ethnographic research design. Data collection was conducted through interviews. The results show that from the perspective of religious moderation, the Sipakatau, Sipakalebbi, Sipakainge' traditions embody values of religious tolerance, peace, mutual respect, understanding of other ethnic cultures, and harmony among religious communities. From the perspective of Islamic law, these traditions contain values of justice, honesty, and ethics in social interactions. The factors influencing the presence of values of religious moderation and Islamic Law in these traditions are due to the strong cultural heritage and local wisdom of the Bugis community in Sorong, Papua, which is passed down to the younger generation, strong religious education, and the involvement of religious and community leaders. Thus, this research is expected to complement previous studies by presenting philosophical values of religious moderation and Islamic Law applied in daily life.